The Emergence of Genome Editing—Innovation Network Dynamics of Academic Publications, Patents, and Business Activities - Laibach, Natalie; Bröring, Stefanie (Frontiers in Bioengineering and Biotechnology, 2022)
Transformative societal change can both be triggered and influenced by both macro-level political means and emergence of technologies. Key enabling technologies and therein biotechnology hold the power to drive those changes forward, evolving from breakthrough academic discoveries into business activities. Due to its increasing empirical relevance, we picked genome editing as an example for an emerging technology and extracted publication, patent, and company data from the years 2000-2020. By drawing upon social network analysis, we identify major networks and clusters that are dominating the respective time and layer. Based on these networks, we draw vertical connections between scientific knowledge, patented technologies, and business activities to visualize the inter-level relationships between actors through technological development. Thereby, we identify network dynamics of the emergence of genome editing, the most important actors and clusters evolving, and its spread into different areas.